2021
DOI: 10.3390/pediatric13030061
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19 Vaccine for Adolescents. Concern about Myocarditis and Pericarditis

Abstract: The alarming onset of some cases of myocarditis and pericarditis following the administration of Pfizer–BioNTech and Moderna COVID-19 mRNA-based vaccines in adolescent males has recently been highlighted. All occurred after the second dose of the vaccine. Fortunately, none of patients were critically ill and each was discharged home. Owing to the possible link between these cases and vaccine administration, the US and European health regulators decided to continue to investigate the potential causal relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Our results indicated that post-COVID-19 vaccine myocarditis and pericarditis adverse events were more prevalent in young males 18-29 years old. Actually, a recent opinion [ 34 ] in the journal Pediatric Reports raised concerns about mRNA vaccines for adolescents, and questioned why cardiac adverse events have higher incidence in male adolescents after receiving the second dose of the vaccine and what mechanisms are contributing to these adverse events. Our data also showed that the number of myocarditis and pericarditis adverse events was higher for Pfizer/BioNTech vaccine followed by Moderna’s and then Janssen’s (based on the available data described herein).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that post-COVID-19 vaccine myocarditis and pericarditis adverse events were more prevalent in young males 18-29 years old. Actually, a recent opinion [ 34 ] in the journal Pediatric Reports raised concerns about mRNA vaccines for adolescents, and questioned why cardiac adverse events have higher incidence in male adolescents after receiving the second dose of the vaccine and what mechanisms are contributing to these adverse events. Our data also showed that the number of myocarditis and pericarditis adverse events was higher for Pfizer/BioNTech vaccine followed by Moderna’s and then Janssen’s (based on the available data described herein).…”
Section: Discussionmentioning
confidence: 99%
“…However, if sponsors do not generate the evidence needed for safe and effective use of their product in all relevant populations, the burden of medical uncertainty is laid upon the groups not represented in the drug development program [ 22 ]. The relevance of this with respect to COVID-19 vaccines is clearly exemplified by the recent observation that suggest a disproportionate higher frequency of post-vaccination myocarditis in adolescents and young adults than in the average adult population [ 23 ].…”
Section: Discussionmentioning
confidence: 98%
“…The EUA has been modified to include information on myocarditis after receipt of mRNA COVID-19 vaccines, with the fact sheets to be provided before vaccination; in addition, CDC has developed patient and provider education materials about the possibility of myocarditis and symptoms of concern, to ensure prompt recognition and management of myocarditis [ 173 , 176 ]. Importantly, none of the patients fulfilled the criteria for multi-system inflammatory syndrome or Kawasaki-like disease and there was no evidence of acute SARS-CoV-2 infection [ 184 ].…”
Section: Possible Side Effects Of Covid-19 Vaccines In Children and Young Peoplementioning
confidence: 99%